Expectativas inflacionárias no regime de metas para a inflação: a experiência brasileira no período 1999-2004 - Nakao, Carlos (2005)
The present work aims to discuss the importance of Central Bank's reputation and credibility inside the Inflation Target Regime. The theory that this monetary solution coordinates the market's expectation is tested using one index that quantifies credibility and Person's coeficient. The numerical data between 1999 and 2004 was extracted from Market's Expectation System. The preliminary findings (once that this time period is very short to definitive conclusions) show the strong relationship between credibility-reputation economic theory and market's inflationary expectation.